The role of socio-demographic and psychological factors in shaping individual carbon footprints in Finland - Sahari,Elisa; Salo, Marja; Sandman, Nils (Springer Science and Business Media LLC, 2025)
Household consumption emissions are a major contributor to global greenhouse gas emissions, making them a vital target for emission reductions. While previous research has studied socio-demographic and situational factors in explaining the variation in individuals’ carbon footprints, a more comprehensive exploration of individual drivers, would benefit the development of effective and equitable mitigation policies. The current study examines associations between psychological and socio-demographic factors and carbon footprints of Finnish adults (n = 3,519). Income was found to be the strongest factor explaining the variation in carbon footprints. While environmental attitudes, perceived easiness and perceived importance of climate actions statistically explained differences in carbon footprints, the effect sizes were modest. The factors explaining variation in the carbon footprint varied across different domains (housing, travel, diet, and other consumption of goods and services), with psychological factors having a more substantial effect on diet compared to other domains. Overall, the findings suggest that tailoring policy interventions to reduce emissions from different domains to specific groups and factors could be beneficial. Furthermore, the greatest emission reduction potential lies among higher-income individuals. In the dietary domain, attitude-changing interventions could be more effective, while financial or choice architecture interventions might be better suited for other domains.